Testis-sparing surgery in an adult with bilateral synchronous seminomatous tumor - (:unkn) unknown (WILEY, 2004)
Bilateral synchronous testicular cancer is a rare occurrence and is usually associated with similar histological findings in each testicle. The standard therapy of bilateral testis cancer is generally considered to be orchiectomy. We present a case of synchronous bilateral testicular germ cell tumor treated with testis-sparing surgery. The patient was disease free for 30 months after surgery without local recurrence or distant metastases. Testis-sparing surgery provides a better quality of life and may be considered a safe, feasible alternative in the treatment of carefully selected patients with bilateral testicular germ cell tumor.
Keywords: bilateral testicular germ cell tumor; synchronous; testis-sparing surgery; PRESERVING SURGERY